2020
DOI: 10.1037/hea0001018
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing prenatal maternal distress with unique prenatal cortisol trajectories.

Abstract: It is widely assumed that glucocorticoids represent a primary mechanism through which exposure to adversity and maternal psychological distress shape prenatal developmental trajectories of both mother and fetus. However, despite repeated investigations and the fact that prenatal cortisol has been reliably linked to developmental outcomes, the empirical evidence supporting an association between prenatal cortisol and maternal distress is scarce. In this study, a novel approach to assessing links between materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
(44 reference statements)
1
18
0
Order By: Relevance
“…This perinatal evidence is consistent with research linking transient mood changes to hypercortisolemia, thereby supporting the utility of examining changes in depressive symptoms and HPA axis function in pregnancy (Penninx et al, 2013). Other studies have also found that maternal prenatal distress is associated with distinct trajectories of cortisol across pregnancy (Peterson et al, 2020) and increases in pregnancy anxiety from mid to late pregnancy correspond to increases in pCRH over the same period (Ramos et al, 2019). Taken together, such evidence demonstrates that patterns of psychological distress during pregnancy show unique associations with changes in physiology over pregnancy.…”
Section: Maternal Depressive Symptoms and Pcrh During Pregnancysupporting
confidence: 82%
See 1 more Smart Citation
“…This perinatal evidence is consistent with research linking transient mood changes to hypercortisolemia, thereby supporting the utility of examining changes in depressive symptoms and HPA axis function in pregnancy (Penninx et al, 2013). Other studies have also found that maternal prenatal distress is associated with distinct trajectories of cortisol across pregnancy (Peterson et al, 2020) and increases in pregnancy anxiety from mid to late pregnancy correspond to increases in pCRH over the same period (Ramos et al, 2019). Taken together, such evidence demonstrates that patterns of psychological distress during pregnancy show unique associations with changes in physiology over pregnancy.…”
Section: Maternal Depressive Symptoms and Pcrh During Pregnancysupporting
confidence: 82%
“…Results of prior studies examining associations between maternal depressive symptoms and pCRH in pregnancy are mixed, likely because measures at single time points or means over the course of pregnancy do not capture important changes in mood and physiology that occur during this time (Glynn, Howl, Fox, 2018;Meltzer-Brody et al, 2011;Rich-Edwards et al, 2008;Susman et al, 1999). Notably, these results add to small but growing evidence that profiles of psychological and physiological change over pregnancy may better capture the links between psychological distress and prenatal stress physiology (e.g., Peterson et al, 2020), thus supporting calls for comprehensive measurement of stress physiology during pregnancy (Giesbrecht et al, 2015;Howland et al, 2016). This study advances our understanding of how prenatal programming of the fetal HPA axis may occur by examining how patterns of maternal psychological distress relate to changes in pCRH as well as infant cortisol reactivity.…”
Section: Discussionmentioning
confidence: 94%
“…There are several plausible mechanisms by which prenatal maternal distress could impact telomere biology during the fetal period, including stress hormones, oxidative stress, and inflammation. Mothers experiencing elevated prenatal distress during pregnancy show atypical cortisol and placental corticotropin‐releasing hormone (CRH) production (Kane et al., 2014; Peterson et al., 2020), and cortisol exposure may mediate the association between distress and newborn TL (Bosquet Enlow et al., 2019). Increased inflammation (D'Anna‐Hernandez et al., 2012; Osborne et al., 2018) and higher oxidative stress (Eick et al., 2018) also have been associated with elevated maternal distress during pregnancy, and there is new evidence that elevated inflammatory markers in pregnancy predict shorter newborn TL (Lazarides et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…nal distress could impact telomere biology during the fetal period, including stress hormones, oxidative stress, and inflammation. Mothers experiencing elevated prenatal distress during pregnancy show atypical cortisol and placental corticotropin-releasing hormone (CRH) production(Kane et al, 2014;Peterson et al, 2020), and cortisol exposure may mediate the association between distress and newborn TL(Bosquet Enlow et al, 2019). Increased inflammation (D'Anna-…”
mentioning
confidence: 99%
“…40 During a normal pregnancy, cortisol levels rise steadily with gestational age; however, in pregnant women with depressive symptoms and high perceived stress, the trajectory of cortisol is characterized by an increase in the first trimester and a sustained high level in the second and third trimesters. 41 Moreover, studies have found that corticotropin-releasing hormone and cortisol levels are higher in pregnant women with depression than those without depression. 42,43 In addition, DNA methylation in the promoter of the gene encoding the glucocorticoid receptor (NR3C1) and its repressor FKBP51 (FKBP5) has been shown to be higher in pregnant women following exposure to intimate partner violence.…”
Section: Discussionmentioning
confidence: 99%